2004
DOI: 10.1016/j.rmed.2004.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone treatment improves body composition and sexual function in men with COPD, in a 6-month randomized controlled trial

Abstract: The aim of this study was to assess the effect of a low-dose testosterone on body composition and pulmonary function, as well as on quality of life, sexuality, and psychological symptoms in patients with chronic obstructive pulmonary disease (COPD). Twenty-nine men with moderate to severe COPD were allocated to receive either 250 mg of testosterone or placebo intra-muscularly, every fourth week, during the 26 weeks study period. Fat-free mass increased in the treatment group (P<0.05), and a significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 32 publications
5
69
1
2
Order By: Relevance
“…The results of our study are consistent with those of some others, 37,38 but other studies have shown positive results of supplementation of testosterone on sexual function. 16,17 A meta-analysis has shown that testosterone use may be associated with small improvements in erectile function and moderate improvement in libido in elderly men.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study are consistent with those of some others, 37,38 but other studies have shown positive results of supplementation of testosterone on sexual function. 16,17 A meta-analysis has shown that testosterone use may be associated with small improvements in erectile function and moderate improvement in libido in elderly men.…”
Section: Discussionsupporting
confidence: 93%
“…Gains in muscle strength and mass in supplemented patients who undertook resistance training were even greater, suggesting a synergistic effect. Svartberg and colleagues compared testosterone supplementation with placebo in 29 men with COPD who were not selected or screened for biochemical hypogonadism at recruitment and did not present with low muscle mass (573). Testosterone was administered intramuscularly every 4 weeks for 26 weeks.…”
Section: Testosterone and Other Anabolic Steroidsmentioning
confidence: 99%
“…Deux études ont évalué l'effet de la testostérone seule, c'est-à-dire non intégrée dans un programme de réhabilitation respiratoire, chez les patients BPCO [68,69] (Tableau 1). Un analogue de la testostérone, l'oxandrolone, a été donné par voie orale à un groupe de 128 patients ambulatoires (57 hommes et 71 femmes) BPCO GOLD II-III (capacité vitale forcée [CVF] < 50 %).…”
Section: Androgénothérapie Seuleunclassified
“…Dans un autre groupe de 29 patients ambulatoires de sexe masculin avec BPCO modérée à sévère (CVF < 60 %), la testostérone a été administrée par voie intramusculaire pendant 26 semaines avec des effets positifs sur la composition corporelle : masse non grasse augmentée de 1,1 kg et masse grasse diminuée de 1,5 % comparativement à l'état basal. Aucun effet n'était observé sur les paramètres respiratoires, tels que gaz du sang artériels, spirométrie, test de marche des 6 minutes et saturation en oxygène nocturne [69]. Néanmoins une amélioration de la fonction érectile et de la qualité de la vie sexuelle était rapportée.…”
Section: Androgénothérapie Seuleunclassified